2021
DOI: 10.1186/s13033-021-00460-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with involuntary psychiatric hospitalization in Portugal

Abstract: Background Identifying which factors contribute to involuntary psychiatric hospitalization may support initiatives to reduce its frequency. This study examines the sociodemographic, clinical, and contextual factors associated with involuntary hospitalization of patients from five Portuguese psychiatric departments in 2002, 2007 and 2012. Methods Data from all admissions were extracted from clinical files. A Poisson generalized linear model estimate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
0
15
0
1
Order By: Relevance
“…As patients suffering from symptoms of acute psychosis present a relevant share of INVOLP, a sound understanding of risk factors contributing to IA in this specific group of patients is clinically relevant. Most previously conducted studies examining predictors of IA have focused on the whole subpopulation of INVOLP which has led most researchers to establish that symptoms associated with psychosis and/or a diagnosis of schizophrenia [5,9,16,19,20,32,33] as well as a diagnosis of an organic mental disorder [2,5,19,20] are relevant contributors to IA. Significantly fewer studies have addressed risk factors specific to patients with acute psychosis [15,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As patients suffering from symptoms of acute psychosis present a relevant share of INVOLP, a sound understanding of risk factors contributing to IA in this specific group of patients is clinically relevant. Most previously conducted studies examining predictors of IA have focused on the whole subpopulation of INVOLP which has led most researchers to establish that symptoms associated with psychosis and/or a diagnosis of schizophrenia [5,9,16,19,20,32,33] as well as a diagnosis of an organic mental disorder [2,5,19,20] are relevant contributors to IA. Significantly fewer studies have addressed risk factors specific to patients with acute psychosis [15,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Non-adherence to (antipsychotic) medication, recognized as one of the most challenging aspects in the treatment of schizophrenia and leading to a greater risk of relapse, hospitalization, and suicide [41], has been associated with a higher incidence of IA [15,20]. The present study found non-adherence to increase risk of IA by a 2.4-fold, whereas other variables (e.g., police escort, use of restraint), which may ultimately be the result of nonadherence and exacerbation of disease, contributed a significantly higher OR.…”
Section: Sociodemographic and Circumstantial Characteristics Of The S...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Portugal, research on the impacts of environmental factors on mental health started two decades ago, driven by research projects such as Health Impact Assessment (HIA) in Employment Strategies (2009)(2010)(2011)(2012)(2013)(2014), SMAILE (2013SMAILE ( -2015, and Mental Health-Crisis Impact (2015-2017). These projects generated insights about the local and economic factors regarding mental health in the context of crisis [54][55][56][57][58][59][60], particularly important and useful evidence to support research and mental health impact assessment during the COVID-19 health crisis [61,62].…”
Section: Introductionmentioning
confidence: 99%